(untitled) (Proceeding of SINERGY, 2026)
This study examines the influence of green marketing and green products on purchase intention among The Body Shop consumers. In the context of increasing environmental awareness, companies are increasingly adopting sustainable business practices. The Body Shop, as one of the pioneers in implementing green business strategies, serves as an interesting case study to analyze how green marketing initiatives and environmentally friendly products affect consumer purchase decisions. This research employs a quantitative approach with survey methods involving 150 respondents who are The Body Shop customers in Indonesia. The data were analyzed using multiple linear regression with SPSS 26. The results indicate that both green marketing (β = 0.412, p < 0.01) and green product (β = 0.386, p < 0.01) have significant positive effects on purchase intention. Green marketing shows a slightly stronger influence compared to green products. The coefficient of determination (R²) of 0.634 indicates that 63.4% of the variation in purchase intention can be explained by green marketing and green product, while the remaining 36.6% is influenced by other factors not examined in this study. These findings provide important implications for companies in developing effective green marketing strategies and improving environmentally friendly product attributes to enhance consumer purchase intention.